The Development of Nursing Research Instruments - Meehanpong, Pranee; Boonsin, Suneerat (Journal of The Royal Thai Army Nurses, 2021)
The process of developing research instruments in nursing is very important. This is because research tools are used to measure the value of a variable or to collect the data of the variable. It helps to transform abstract concepts into statistical, quantitative or qualitative data. Nursing variables, especially psychological variables, attitudes, behaviors, emotions, and attributes. In social science and management science, researchers cannot measure the variables or need to measure directly differently. Scientific and mathematical measurement. Therefore, nursing researchers must have a good understanding of the research tool development process. To be able to accurately create nursing research tools and get answers to research that meets the objectives of the research. It is important to identify the quality of the research.